2010
DOI: 10.1021/ie901721w
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Properties of Families of Materials

Abstract: A general and useful regularity exists between the properties of families of chemical species: the properties of the members of one family are shown to be simply, and approximately linearly, related to the properties of analogous materials in similar families. As examples, the phenomenon is shown to enable accurate predictive correlations from small amounts of data for the liquid/vapor critical temperatures of several families of organic molecules and for the normal boiling temperatures of SF5- and CF3-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…For these properties the n ‐alkane series cannot be used as reference series, and other reference/target pairs were used. Similarly to the conclusions reached in this study, Peterson found that that the reference series method is particularly useful when one series has more or better data than do other series, and it is most beneficial for determining outliers and incorrect data (consistency analysis).…”
Section: Extension Of the Reference Series Methods To Model Additionalsupporting
confidence: 75%
See 2 more Smart Citations
“…For these properties the n ‐alkane series cannot be used as reference series, and other reference/target pairs were used. Similarly to the conclusions reached in this study, Peterson found that that the reference series method is particularly useful when one series has more or better data than do other series, and it is most beneficial for determining outliers and incorrect data (consistency analysis).…”
Section: Extension Of the Reference Series Methods To Model Additionalsupporting
confidence: 75%
“…Peterson recommended the use of the reference (or analogous) series method to a wider range of families of materials, such as families of organic molecules of the form R 1 XR 2 , containing different functional groups X with R 1 and R 2 representing either branched or linear alkyl groups. He also demonstrated the use of the method for several properties not mentioned here: gas solubility in liquids, GC retention times, Henry's law constants and infinite activity coefficients.…”
Section: Extension Of the Reference Series Methods To Model Additionalmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach used in this paper to evaluate the missing data is to identify trends within and among families of compounds, and to use these trends to estimate needed data. The idea of family trends has been noted by Mathias and Watanasiri [9], is used by the DIPPR 801 project to evaluate and estimate pure-component data [10], and has been used to understand and estimate missing data by Mathias et al [11], and Peterson [12]. Similar to the work of Mathias et al [11] this paper uses molecular simulations to improve estimation techniques.…”
Section: Introductionmentioning
confidence: 97%
“…This similarity can be used for improving the prediction for series for which an insufficient amount of and/or low-precision data are available. For such situations, relying on the suggestions of Peterson 15,16 , Shacham et al 17 developed the "Reference Series" method. Using this method, experimental (if available) or predicted data of a "reference" homologous series for which the largest amount and highest precision experimental data are available, are used as the basis for prediction of properties for other (target) series.…”
Section: C 2013 American Institute Of Chemical Engineersmentioning
confidence: 99%